Perpaduan Budaya dan Sosial Dalam Strategi Patrick Kluivert di Timnas Indonesia Untuk Lolos Ke Piala Dunia 2026 - Taufiq Hidayat (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to analyze the integration of cultural and social elements in the strategies implemented by Patrick Kluivert in the Indonesian national football team's efforts to qualify for the 2026 FIFA World Cup. A phenomenological approach with a qualitative research design was employed to understand the dynamics between local Indonesian culture and the playing tactics adopted by Kluivert. The findings reveal that integrating gotong royong (mutual cooperation) into the playing strategy significantly impacts team cohesion, enhances communication among players, and strengthens unity within the team. The spirit of nationalism and supporter support also plays a vital role in boosting the players' fighting spirit, creating a positive atmosphere on the field. Additionally, the Total Football philosophy, adopted from the Netherlands, introduces flexibility and dynamic play, which aligns well with the characteristics of the Indonesian national team. In conclusion, the success of the Indonesian national team in reaching the 2026 World Cup relies not only on technical skills but also on strengthening social and cultural aspects. This study suggests enhancing youth development, integrating both technical and social aspects in training programs, and reinforcing relationships between players, coaches, and supporters to support the national team's international achievements.